Preserving heritage and technical professional motivation of antiquary workers - Núñez Pardo, Pedro Juan (Transformación, 2024)
This research was conducted at "Francisco Sánchez Betancourt" trade school. It is aimed at developing environmental education and professional and technical motivation by means of the heritage preserving work in masonry trainees. Theoretical research methods were used for systematizing referents, likewise observation, interviews, surveys and experiments were used to advance the proposal consisting of a system of tasks for the subject "Technology of Masonry" based on organized visits to historical buildings and sites. These visits allow masonry trainees to know about the importance of preserving heritage the ways to accomplish it. In addition lectures, video showing sections, book sales and other activities were carried out for promoting students enrolment.
Keywords: Heritage; environmental education; environment; professional training; professional motivation